The Effect Of Hypnosis As Supportive Or Primary Psychotherapeutic Intervention In Some Psychosomatic Conditions - Saifuddin, Shabbir Hussain; Singh, Reena (Journal of Neonatal Surgery, 2025)
Psychosomatic diseases, where psychological factors play a significant role in physical well- being, remain a significant global health problem and are frequently underpinned by emotional dysregulation and chronic stress. Cognitive behavioural therapy (CBT) and mindfulness-based stress reduction (MBSR), two established forms of psychotherapy, have demonstrated their value in the management of disease-related to stress; however, hypnosis's clinical application remains somewhat under-exploited and less researched. The role of hypnosis as a primary or adjunct psychotherapy intervention for psychosomatic diseases is to be systematically examined in this study. Six significant scholarly databases from which this study derives its findings from literature between 2000 and 2024 through a Systematic Literature research (SLR) method are PubMed, PsycINFO, ScienceDirect, SpringerLink, Scopus, and Google Scholar. This research analyzes 56 peer-reviewed articles that explore the clinical outcomes, psychological benefits, therapeutic techniques, and mechanisms of hypnotherapy. As per the study, hypnosis influences neurophysiological, cognitive, and autonomic processes to alleviate symptoms, enhance emotional resilience, and decrease stress. Techniques of common hypnotic practice, such as ego-strengthening, self-hypnosis, posthypnotic suggestion, and guided imagery, have been found to promote emotional control, reduce anxiety and depressive symptoms, and improve the overall psychological well-being of patients. In addition, hypnosis is a popular, non-invasive, and safe treatment with minimal side effects and wide extension to a wide range of patient conditions. The study does identify a number of key challenges, though, including the lack of formal treatment protocols, differences in methodological design, and the ongoing stigma surrounding hypnotherapy. Large randomised controlled trials, the integration of hypnotherapy with standard therapy, and further research into the brain mechanisms of hypnosis are all high priorities for future research. The therapeutic applications of hypnosis in psychosomatic treatment are emphasized here, and a case is also presented for its increased incorporation into present-day psychotherapeutic practice.. .